Emergency Department Visits for Acute Pancreatitis in Children. Issue 4 (April 2015) - Pant, Chaitanya; Deshpande, Abhishek; Sferra, Thomas J.; Gilroy, Richard; Olyaee, Mojtaba
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to describe the epidemiology and trends in pediatric acute pancreatitis (AP)–associated emergency department (ED) visits in the United States. Methods Estimates of AP–associated ED visits were calculated in children from birth to 19 years of age using the Nationwide Emergency Department Sample. Results From 2006 to 2011, there were an estimated total of 78, 787 ED visits associated with the diagnosis of AP. The greatest number of ED visits occurred in children 15 to 19 years of age (67.0%). A majority of patients were subsequently admitted to the hospital for further care (74.1%). Risk factors independently associated with an increased rate of hospital admission included 3 or more comorbid conditions (adjusted odds ratio [aOR] 12.81; 95% confidence interval [CI], 11.29–14.56), children younger than 5 years (aOR, 1.73; 95% CI, 1.58–1.89), presentation to a teaching hospital (aOR, 1.68; 95% CI, 1.62–1.74) or a hospital in the Western region of the United States (aOR, 1.48; 95% 1.42–1.54), and health coverage with Medicaid (aOR, 1.23; 95% CI, 1.17–1.29). Acute pancreatitis–associated ED visits increased from 14.5 per 100, 000 children in 2006 to 16.1 per 100, 000 children in 2011 (11.42% increase; P < 0.01). Conclusion There has been an increasing incidence of AP-associated ED visits in children from 2006 to 2011.